The health and wellness benefits of traditional postnatal Practice (tpc) on postnatal mothers: a systematic review - Patricia Sator; Rohani Mamat; Syed Sharizman Syed Abdul Rahim; Kim Geok-Chan; Rosalia Saimon; Sukhbeer Kaur A/P Darsin Singh; Waidah Sawatan (UPM, 2022)
Introduction: Postnatal is a transition process for the mother back to her non-pregnancy state and involves the changes in hormones level. During the postnatal period, many health issues need to be addressed for both mother and newborn. One of the upsetting health issues for the mother due to the increasing trend is postnatal depression and if it is not identified and treated early, it may cause further complicated problems not only to the mother but also to the baby, family, and local community. With this issue, the Ministry of Health Malaysia has taken a few initiatives to encourage the postnatal mother to also practice the non-medical approaches or traditional postnatal care (TPC) as a self-care for the prevention of postnatal depression. Aim: To systematically identify and review studies examining the influence of TPC on postnatal mothers. Design & Data Sources: A systematic search strategy on the research trend for the period between the years 2013 to 2020 through the Scopus database, Science Direct, and PubMed database. Methods: This review has identified 7 journal articles based on the preferred reporting items for the systematic reviews (PRISMA) framework. Results: There are many methods of TPC, such as traditional postnatal body massage, herbal consumption, herbal bath, body steaming, and body wrapping based on own culture and beliefs. Besides the TPC preparation and techniques, some studies also describe the effects of TPC on a mother’s health and wellness. Conclusion: TPC shows encouraging health trends, and it helps to enhance the well-being and good health of postpartum mothers.